Natural history and predictors for progression of mild childhood obstructive sleep apnoea. Issue 1 (23rd September 2009) - Li, A M; Au, C T; Ng, S K; Abdullah, V J; Ho, C; Fok, T F; Ng, P C; Wing, Y K
Abstract : Aims: The natural history of mild childhood obstructive sleep apnoea (OSA) was examined and factors associated with disease progression were identified. Methods: Subjects were recruited from an epidemiological study which examined the prevalence of OSA in Chinese children aged 6–13 years. The first 56 consecutive children identified with mild OSA (apnoea-hypopnoea index 1–5) were invited for a repeat assessment 2 years after the diagnosis. Results: 45 children participated in the follow-up study, in 13 of whom (29%) the OSA was found to have worsened. Compared with those in whom OSA had not worsened, the worsened OSA group had a greater increase in waist circumference, a higher prevalence of large tonsils (occupying ⩾50% of the airway) at both baseline and follow-up, and a higher prevalence of habitual snoring at both baseline and follow-up. The presence of large tonsils had a positive predictive value of 53% and a negative predictive value of 83% for worsening OSA over a 2-year period. Multivariate linear regression analysis showed that the change in obstructive apnoea-hypopnoea index was associated with age at baseline (β (SE) = −0.92 (0.34), p = 0.009), gender (male = 1; female = 0) (β (SE) = 4.69 (1.29), p<0.001), presence of large tonsils at baseline (β (SE) = 4.36 (1.24), p = 0.001), change in waist circumference (β (SE) = 0.30 (0.09), p = 0.002) and persistently large tonsils (β (SE) = 5.69 (1.36), p<0.001) over the 2-year period. Conclusions: Mild OSA in the majority of children does not resolve spontaneously. Subjects with tonsillar hypertrophy, especially boys, should be closely monitored to allow early detection of worsening OSA. Weight control should be stressed in the management of childhood OSA.